(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article highlights the basic ideas about β-thalassemia accumulated to date. The main characteristics of this pathology, the genetic basis and characteristics of mutant alleles of β-thalassemia are given. Data on mutations in β-thalassemia obtained by sequencing and the role of mutations in the development of this pathology are provided. β-thalassemia is an autosomal recessive disease characterized by hypochromic hemolytic anemia and dependence on blood transfusions for life-saving reasons [4, 10].